1997
DOI: 10.1088/0256-307x/14/6/013
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Aggregation Behavior in Amorphous Silicon Nitride Films

Abstract: A &actid aggregation behavior in amorphous silicon nitride (Si,N,) films deposited by microwave electron cyclotron resonance plasma chemical vapor deposition is reported. The fractal structure and dimension of 1.45 obtained by experiment and computer simulation are all in excellent agreement with the result predicted by the cluster-cluster-aggregation model. Theforming of &actid structure is related to the change of discharge mode between ring plasma and bulk plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The optical gap of amorphous -α α fluorinated carbon films is relatively low ranging from 1.1 eV to 3.98 eV. [40][41][42][43] These values are much smaller than the direct gap of pure tetrahedrically bonded carbon (6.9-7.25 eV). 44 The E og of amorphous fluorinated carbon is closely related to size volume distribution of graphitic carbon clusters in an optically transparent matrix of amorphous material.…”
Section: Optical Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…The optical gap of amorphous -α α fluorinated carbon films is relatively low ranging from 1.1 eV to 3.98 eV. [40][41][42][43] These values are much smaller than the direct gap of pure tetrahedrically bonded carbon (6.9-7.25 eV). 44 The E og of amorphous fluorinated carbon is closely related to size volume distribution of graphitic carbon clusters in an optically transparent matrix of amorphous material.…”
Section: Optical Propertymentioning
confidence: 99%
“…39 It has been reported that the π-bonds, showing sp 2 coordination in graphitic carbon clusters of sixfold rings, lower the optical energy gap in amorphous carbon films including hydrogenated or fluorinated carbon films. [40][41][42][43][44][45][46] SiCF films show the aromatic carbon double bonds at 1500-1600 cm Ϫ1 in Fig. 3.…”
Section: Optical Propertymentioning
confidence: 99%